2012
DOI: 10.1007/s10853-012-6435-x
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of hybrid solar cells using poly(2,5-dimethoxyaniline) hexagonal structures and zinc oxide nanorods

Abstract: Flower-shaped zinc oxide (ZnO) structures have been synthesized in a microwave at 180°C for 20 min using zinc nitrate and KOH. Detailed structural and morphology observation showed that the micron-sized ZnO nano-pencils grow out of the base of the flower-shaped ZnO structures. Photoluminescence spectrum measured at room temperature showed a sharp UV emission band around 390 nm which is attributed to the radiative annihilation of excitons. The synthesized PDMA and ZnO nanopencils are highly crystalline material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Nanomaterials have extremely small feature sizes, typically in the order of less than 200 nm. Currently, one-dimensional nanomaterials have been studied extensively because of their exceptional properties and potential applications in the electronics [1][2][3], pharmaceuticals [4], biological [5], as catalysis and as miniaturized magnetic devices due to their tiny sizes [6][7][8], which exhibit flexibility and stretchable devices [9], and as well as energy conservation efficiency [10]. It has been studied widely since the discovery of carbon nanotube by Iijima [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Nanomaterials have extremely small feature sizes, typically in the order of less than 200 nm. Currently, one-dimensional nanomaterials have been studied extensively because of their exceptional properties and potential applications in the electronics [1][2][3], pharmaceuticals [4], biological [5], as catalysis and as miniaturized magnetic devices due to their tiny sizes [6][7][8], which exhibit flexibility and stretchable devices [9], and as well as energy conservation efficiency [10]. It has been studied widely since the discovery of carbon nanotube by Iijima [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…33−35 ZnO has various characteristics, for instance, easy synthesis, low cost, high mobility, and tunable morphology. 33 In our research, we fabricate hybrid BHJ solar cells by using ZnO QDs modified with liquid-crystalline ligands, 4′-hydroxy-[1,1′-biphenyl]-4-carbonitrile (cbp), as electron acceptors and conjugated rod− rod diblock copolymers comprising a regioregular P3HT segment and a side-chain liquid-crystalline polythiophene segment bearing cyanobiphenyl mesogenic pendants (PTcbp), polythiophene-b-poly{3-[10-(4′-cyanobiphenyloxy)-decyl]thiophene} (P3HT-b-PTcbp), as electron donors. Because of the self-assembly and crystallinity of each conjugated segment and the interaction between the cbp ligands on the surface of ZnO QDs and cyanobiphenyl sidechain mesogens of P3HT-b-PTcbp, we expect to observe fine dispersion and self-assembly of ZnO QDs in a polymer matrix, an intimate contact between the conjugated polymer and QD phases, and improvement of the photovoltaic properties of the hybrid devices.…”
Section: Introductionmentioning
confidence: 99%
“…Although there was considerable interest in the co-self-assembly of block copolymers with QDs for optical and electronic applications, conjugated rod–rod diblock copolymers bearing side-chain mesogens had not been applied in hybrid BHJ solar cells. On the other hand, previously it had been demonstrated that photoinduced charge transfer can occur between a conjugated polymer and zinc oxide (ZnO) QDs effectively. ZnO has various characteristics, for instance, easy synthesis, low cost, high mobility, and tunable morphology . In our research, we fabricate hybrid BHJ solar cells by using ZnO QDs modified with liquid-crystalline ligands, 4′-hydroxy-[1,1′-biphenyl]-4-carbonitrile (cbp), as electron acceptors and conjugated rod–rod diblock copolymers comprising a regioregular P3HT segment and a side-chain liquid-crystalline polythiophene segment bearing cyanobiphenyl mesogenic pendants (PTcbp), polythiophene- b -poly{3-[10-(4′-cyanobiphenyloxy)decyl]thiophene} (P3HT- b -PTcbp), as electron donors.…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been a few reports on the synthesis of flower‐like ZnO structures [27–31]. More recently, Mavundla et al fabricated the solar cell devices from flower‐shaped ZnO structures synthesized by microwave annealing of zinc nitrate and KOH at 180 °C [32]. Chen et al reported a dye‐sensitized solar cell based on a flowerlike ZnO nanorod array photo anode fabricated by low temperature hydrothermal method [33].…”
Section: Introductionmentioning
confidence: 99%